Reining in Self-Leadership within Academia and Athletics: A Self-Determination Perspective - Seidel, Laura; Sullivan, Rebecca; Baker, Amanda; Blanchard, Céline (Applied Psychology Review, 2023)
The purpose of this paper is to examine self-leadership and its antecedents through a self-determination theory framework in order to identify and understand the key mediators that contribute to the development of self-leadership. Two studies were used to test the tenability of our proposed model across two domains. Study 1 examined self-leadership amongst a sample of undergraduate students. Study 2 examined a similar model amongst equine athletes from across Canada. Self-report questionnaires were employed to collect all data. Based on the conclusions, we suggest that autonomous motivation, rational decision-making and emotional regulation are important aptitudes for the development of efficient self-leadership. Ultimately, the research expands the literature on both self-determination theory and self-leadership by offering a unique multiple mediation models for predicting self-leadership development.